Understanding mental toughness in Australian soccer: Perceptions of players, parents, and coaches - Coulter, T.; Mallett, C.; Gucciardi, Daniel (Routledge, 2010)
We explored mental toughness in soccer using a triangulation of data capture involving players (n = 6), coaches (n = 4), and parents (n = 5). Semi-structured interviews, based on a personal construct psychology (Kelly, 1955/1991) framework, were conducted to elicit participants' perspectives on the key characteristics and their contrasts, situations demanding mental toughness, and the behaviours displayed and cognitions employed by mentally tough soccer players. The results from the research provided further evidence that mental toughness is conceptually distinct from other psychological constructs such as hardiness. The findings also supported Gucciardi, Gordon, and Dimmock's (2009) process model of mental toughness. A winning mentality and desire was identified as a key attribute of mentally tough soccer players in addition to other previously reported qualities such as self-belief, physical toughness, work ethic/motivation, and resilience. Key cognitions reported by mentally tough soccer players enabled them to remain focused and competitive during training and matches and highlighted the adoption of several forms of self-talk in dealing with challenging situations. Minor revisions to Gucciardi and colleagues' definition of mental toughness are proposed. © 2010 Taylor & Francis.